Bed bug infestation in a French university hospital: control strategy, financial impact and perspectives. (August 2022) - Gressier, A.; Galakhoff, N.; Thuillier, P.; Kerlan, V.; Cogulet, V.; Cosse, M.; Daniel, L.; Canevet, M.; Cabon, S.; Le Grand, A.; Baron, R.; Saliou, P.
Summary: Background: With the increase in international travel and development of insecticide resistance, a re-emergence of the bed bug has been observed since the 2000s and it is becoming a worldwide public health problem. Hospitals and other medical settings have not been spared, while the cases reported remain limited. However, there are no specific recommendations for the healthcare settings in the literature. Aim: To report our experience of a bed bug infestation in a medical unit, in the French University Hospital Centre of Brest, caused by the admission of a patient carrier in October 2020. We described the practical methods used to control bed bugs infestation, evaluated the cost of this episode and created a specific procedure to take care of at-risk patients or known carriers of bed bugs. Findings: The decision to close the unit for global treatment was taken after the investigations using a sniffer dog revealed that four rooms were infested. The closure lasted 24 days. We estimated the total cost of the infestation to be approximately US$400, 000. No other wave of infestation occurred. We created a specific protocol of care for patients who were known carriers or at risk of carriage of bed bugs to graduate a strategy of control. Conclusion: Bed bug infestations in health facilities have a major impact on the care of patients and relevant economic consequences. Prevention and education policies are an essential starting point to respond to the scale of the phenomenon.